2008
DOI: 10.1074/jbc.m704328200
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Chloride-losing Diarrhea Causing Mutations in the STAS Domain Result in Misfolding and Mistrafficking of SLC26A3

Abstract: Congenital chloride-losing diarrhea (CLD) is a genetic disorder causing watery stool and dehydration. Mutations in SLC26A3 (solute carrier 26 family member 3), which functions as a coupled Cl ؊ /HCO 3 ؊ exchanger, cause CLD. SLC26A3 is a membrane protein predicted to contain 12 transmembranespanning ␣-helices and a C-terminal STAS (sulfate transporters and anti-sigma-factor) domain homologous to the bacterial anti-sigma-factor antagonists. The STAS domain is required for SLC26A3 Cl ؊ /HCO 3 ؊ exchange function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 63 publications
6
74
0
Order By: Relevance
“…3E), which is known to be required for both the activity and biosynthesis/stability of the transporter. Indeed, other mutations at conserved positions in the STAS domain have been shown to cause congenital chloride diarrhea (23). This mutation was absent among 190 control chromosomes.…”
Section: Mutation In Slc26a3mentioning
confidence: 99%
“…3E), which is known to be required for both the activity and biosynthesis/stability of the transporter. Indeed, other mutations at conserved positions in the STAS domain have been shown to cause congenital chloride diarrhea (23). This mutation was absent among 190 control chromosomes.…”
Section: Mutation In Slc26a3mentioning
confidence: 99%
“…Second, mutations of the N-terminal end of the ␣-helical regions was associated with impaired function despite expression at the plasma membrane (64). A more recent study of disease-associated mutations in the STAS domain of SLC26A3 indicates a predominant effect on biosynthesis, affecting different steps in the folding and/or trafficking pathway of the protein (16). We have also found that single nucleotide polymorphisms in human SLC26A9 flank the STAS domain and that at least one seems to reduce SLC26A9-mediated transport (65).…”
Section: And E)mentioning
confidence: 99%
“…Slc26a9 protein has been localized to epithelia of the stomach and lung (9,10,14), although mRNA is also detectable in brain, heart, kidney, small intestine, thymus, and ovary (10). The R-region of CFTR was previously shown to increase the activity of Slc26a3 and Slc26a6 by interaction with STAS domains (6,15,16). Because Slc26a9 displays several different modes of ion transport, we asked if the R-region of CFTR would also increase the activity of Slc26a9.…”
mentioning
confidence: 99%
“…The mechanistic role of SpoIIAA phosphorylation remains unclear, because substitution of this serine residue by acidic residues did not phenocopy the activity of serine phosphorylation (24,25,27). The STAS domains of human SLC26A3 (29) and human SLC26A9 (53) interact in vitro with the phosphorylated R domain of CFTR, but the reported regulatory interactions of SLC26 polypeptides and CFTR in vitro and in vivo have varied. PKC phosphorylation of the human SLC26A6 STAS domain has been suggested to regulate Cl Ϫ /HCO 3 Ϫ exchange activity through CAII binding (54), but this phosphorylation did not regulate oxalate transport (55), and its relationship to CFTR is unknown.…”
mentioning
confidence: 99%
“…Published prelim-inary structures of additional STAS domain proteins include the NMR solution structure of Thermotoga maritima putative anti-antagonist TM1442 in phosphorylated and unphosphorylated states (26), the NMR and crystal structures of T. maritima putative anti-antagonist TM1081 (27), and the crystal structure of the putative stressosome component RsbS from Moorella thermoacetica (28). The SpoIIAA structure has been used to model the eukaryotic SLC26 STAS domain, including congenital chloride diarrhea missense mutations in the human SLC26A3 domain that result in subtle chemical shift changes as detected by 1 H-15 N two-dimensional HSQC NMR (29). However, the amino acid assignments of this structure have not been reported and, until recently, no other structural information had been released for STAS domains of SulP/SLC26 anion transporters.…”
mentioning
confidence: 99%